Guardians of the Galaxy. Galaxy's most wanted - Scott, Mairghread; Allor, Paul; Caramagna, Joe; Caramagna, Joe (Marvel Worldwide, Incorporated, 2015)
Follows the further adventures of the Guardians of the Galaxy.